2016
DOI: 10.1002/jcla.22071
|View full text |Cite
|
Sign up to set email alerts
|

Rapid differentiation of cocci/mixed bacteria from rods in voided urine culture of women with uncomplicated urinary tract infections

Abstract: Through laser flow cytometry, we can predict growth of cocci/mixed growth in the pre-analytical phase of urine culture, thus avoiding unnecessary urine culture and waiting time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…The unnecessary use of antibiotics can be avoided because these results can be obtained faster than the results of urine cultures. Previous studies [8][9][10][11][12][13][14] have shown reliable and valid results using the Sysmex UF-1000i system, which is comparable to the urine culture and microscopic counting results [15].…”
supporting
confidence: 60%
“…The unnecessary use of antibiotics can be avoided because these results can be obtained faster than the results of urine cultures. Previous studies [8][9][10][11][12][13][14] have shown reliable and valid results using the Sysmex UF-1000i system, which is comparable to the urine culture and microscopic counting results [15].…”
supporting
confidence: 60%
“…For that, microscopy findings of urine sediment with or without Gram staining is recommended, not only to ensure diagnostic accuracy, but also to distinguish between those forms. In the future, flow cytometry may take the place of microscopy, because a system for discriminating between Gram-positive and negative bacteria has been developed and may be available soon for clinical use [32].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a different approach might be required. Two trials used different patterns of bacteria fluorescent light to predict bacterial morphologies and mixed flora correctly using UF1000i (Sysmex, Kobe, Japan) [ 23 , 24 ]. While Yang, Yang [ 24 ] concluded that results of laser flow cytometry predict growth of mixed flora, the results of Geerts, Jansz [ 23 ] showed underperformance in the category mixed flora.…”
Section: Discussionmentioning
confidence: 99%
“…Two trials used different patterns of bacteria fluorescent light to predict bacterial morphologies and mixed flora correctly using UF1000i (Sysmex, Kobe, Japan) [ 23 , 24 ]. While Yang, Yang [ 24 ] concluded that results of laser flow cytometry predict growth of mixed flora, the results of Geerts, Jansz [ 23 ] showed underperformance in the category mixed flora. Further studies are needed to clarify the results of this promising approach and give recommendations for the use in clinical practice which is of special use in the emergency setting where the contamination rate is often found to be high [ 25 ].…”
Section: Discussionmentioning
confidence: 99%